Learning peace and citizenship through narratives of war? - Vesterdal, Knut (JSSE - Journal of Social Science Education, 2023)
Purpose: The article explores the roles of war and violent conflicts in citizenship education. Approach: This is a theoretical article, drawing on literature from the interdisciplinary fields of political science, history, citizenship education as well as field studies in different learning arenas, war memorial sites- and museums Findings: There are divergent roles of war in citizenship education, and the typology of five didactic perspectives illustrates the challenges concerning the types of citizenship it aims at. Narratives of war could produce and contribute to different forms of citizenship or even represent the opposite of the concept Research limitations: Further empirical research is needed to develop knowledge on how to deal with war and conflict in educational practice, both in schools and other learning arenas. Practical implications: The article contributes to addressing and structuring the challenges and potentials of didactic approaches to war and violent conflict in citizenship education.